A cognitive-behavioural program (one day a week) for patients with obesity and binge eating disorder : short-term follow-up data - Adriaens, An (Array, 2008)
Summary: This paper describes an innovative cognitive behavioural program for the treatment of patients with binge eating disorder in the University Psychiatric Center K.U. Leuven Campus Kortenberg in Belgium. The program runs one day a week during 6 months and consists of 24 sessions. The most important therapeutic goals are: (1) normalization of eating habits and stopping the binge eating episodes; (2) promoting physical activity and a positive body experience; (3) learning specific skills such as assertivity, installing a functional self-evaluation system; learning to identify, tolerate and express negative emotions, promoting self-esteem and prevention of relapse. Overall, the goal is to promote both physical and psychological well-being and quality of life. Some preliminary research data on the effectiveness of this program are described. Despite a rather limited weight loss, the number of binges per week decreased significantly, which was the main therapeutic goal of the treatment. Furthermore, the results show some promising improvements on different psychological parameters in BED patients